Sungkai Leaf Potential as Herbal Medicine - Sadakata Sinulingga; Fatmawati Fatmawati; Subandrate Subandrate; Irfannudin Irfannudin; Susilawati Susilawati; Rini Yana (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Indonesia is a tropical country that has biodiversity. One of the biodiversity in Indonesia is the availability of many medicinal plants. The Indonesian Ministry of Health has released a formulary of Indonesian medicinal plants in 2017. One of the plants that has medicinal properties is the sungkai plant. Sungkai plants grow in most parts of Indonesia, including South Sumatra. This plant is also often planted in the yard as a shade. Empirically, sungkai leaves have been used as medicine by various tribes in Indonesia. People use boiled water from sungkai leaves or crushed sungkai leaves as herbal medicine. The phytochemical content of sungkai leaves includes alkaloids, flavonoids, triterpenoids, steroids, phenols and saponins. The results of various studies show that sungkai leaves have benefits as anti-fever, antimalarial, antibacterial and antioxidant. Sungkai leaves also have the ability to increase endurance, so they can be used to fight infectious diseases including Covid19. Sungkai leaves can be used for herbal medicine either as a preventive or therapeutic agents. Further development for the use of Sungkai plants as medicine needs to be done to assess side effects and therapeutic effects more efficiently.